2022
DOI: 10.3390/vaccines10091495
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines Administration in the Perspective of Patient Safety and Quality of Healthcare: Lesson from the Experience of an Italian Teaching Hospital for Pandemic Preparedness

Abstract: The development and administration of vaccines against COVID-19 was a key element in the fight against the pandemic, as it protected health systems and helped restore global economies. National implementation plans and vaccination strategies for COVID-19 vaccines ensured the immunization of large segments of the population in the shortest time. However, even before the start of the vaccination campaign, it was clear to decision-makers that the usual methods of vaccination were not suitable. The aim of this rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The overall satisfaction of the vaccination centre staff and the perception of the workload as neither lower nor higher than usual testify to the fidelity of the implementation. Similar to the report of De Micco et al, our results indicate a strong sense of team spirit and commitment by the centre’s staff, hence underlining the role of leadership and personnel management beyond the formative fulfilment of the required tasks [ 19 ]. This aspect is particularly crucial for consideration upon implementing a human resource strategy based on planned duty roster, as Hrehova et al report a relatively higher incidence of self-reported burnout symptoms among HCWs assigned to work at a mass vaccination centre as part of their regular jobs rather than voluntarily [ 32 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The overall satisfaction of the vaccination centre staff and the perception of the workload as neither lower nor higher than usual testify to the fidelity of the implementation. Similar to the report of De Micco et al, our results indicate a strong sense of team spirit and commitment by the centre’s staff, hence underlining the role of leadership and personnel management beyond the formative fulfilment of the required tasks [ 19 ]. This aspect is particularly crucial for consideration upon implementing a human resource strategy based on planned duty roster, as Hrehova et al report a relatively higher incidence of self-reported burnout symptoms among HCWs assigned to work at a mass vaccination centre as part of their regular jobs rather than voluntarily [ 32 ].…”
Section: Discussionsupporting
confidence: 87%
“…The number of vaccine doses inoculated in the centre every day corresponds to the rate in the COVID-19 hospital-based or mass vaccination sites [ 16 , 19 , 20 ]. It should, however, be noted that our centre operated, even in its initial phase, with a rather limited number of personnel for the inoculations compared to the centres described in the literature so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research illuminates the universality of safety awareness among healthcare providers in Riyadh, Saudi Arabia, thereby signaling a call to action for the healthcare industry. The need to elevate safety culture remains an ever-present objective that necessitates concerted efforts from all stakeholders [33][34][35][36][37][38]. Therefore, the insights from this study act as a clarion call, urging us to continually strive for the advancement of safety culture in healthcare, steering us towards a safer future for all.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, in the initial stages of the vaccination campaign, in the absence of data relating to trials on pregnant women, we believe it was incorrect to provide for compulsory vaccination also for pregnant women. This theme will have to be the subject of discussion and prediction of operating models, to adopt the right behavior in the ethics of a job well done perspective [42].…”
Section: The Legislative Paradoxmentioning
confidence: 99%